Regionalism and Revision : the Crown and its Provinces in England 1250-1650. - Fleming, Peter (Bloomsbury Publishing, 1998)
Historians of premodern Europe often think in terms of ''small worlds'': a series of regional societies functioning independently of each other. This approach works well for isolated areas but is less obviously applicable to England, the most centralised country in Europe. How far England was centrally controlled and how far power in reality remained in the localities are key considerations in understanding English history both in the middle ages and afterwards. The essays in Regionalism and Revision all address these questions, both by analysing how the problem should be approached a.